TECHNOLOGIES FOR ENHANCING CUSTOMER INTERACTION AND SALES EFFICIENCY THROUGH DIGITAL MARKETING TOOLS. (Innovate Conferences, 2025)
In the era of digital transformation, businesses are increasingly leveraging digital marketing tools to build meaningful customer relationships and improve sales efficiency. This research investigates how modern digital marketing technologies contribute to enhanced customer interaction and sales performance, focusing on small and medium-sized enterprises (SMEs). Using a multi-method approach combining surveys, content analysis, and correlation analysis, the study highlights key strategies such as CRM systems, personalized content, email marketing, chatbots, and AI-powered targeting. Findings reveal that enterprises with integrated digital marketing systems experience significant improvements in customer engagement, loyalty, and sales conversion rates. The study recommends a strategic implementation of these technologies as a pathway toward sustainable competitiveness in the modern marketplace.